Case report: Systemic presentation of ALK-positive Histiocytosis - Wei, Yongbao; Zhang, Ruochen; Lin, Deng; Chen, Xiaoyan; Li, Lizhi; Huang, Haijian (Frontiers in Oncology, 2024)
ALK-positive Histiocytosis (ALK-HSs) is a recently identified rare clinical entity characterized by tissue histiocytic alterations associated with ALK gene rearrangement. Clinical presentations can be solitary, multifocal, or systemic (involving multiple sites and organs). Due to limited reported cases, there is inadequate understanding of this disease. This report presents a case of ALK-HSs in a 71-year-old male patient who presented with hematuria for one week. Imaging studies conducted at an external hospital showed multiple lesions in the penis, bilateral testes, back skin, and the third lumbar vertebra. Histopathological findings included spindle and histiocytic cell proliferation with mild or indistinct cellular atypia, interstitial infiltration of lymphocytes, plasma cells, foamy histiocytes, and fibrous tissue proliferation. Immunohistochemistry of the lesion cells revealed positivity for CD68, CD163, ALK1, ALK (D5F3), and Vimentin. FISH testing indicated ALK gene separation in the lesion cells. NGS testing identified the fusion genes KIF5B(NM_004521) and ALK(NM_004304) in the lesion cells. We combined the characteristics of this case with a review of the literature to enhance our understanding of this rare clinical entity.